Identifying Attention Deficit Hyperactivity Disorder (ADHD) Children and Effective Teaching Strategies That Develop Their Multiple Intelligences - Yenny Kristanto (research, training and philanthropy institution Natural Aceh, 2023)
Many of us sometimes fail or misinterpret ADHD children by not understanding fully their traits and symptoms. As a result, many ADHD children are viewed as marginal students at school since they can’t meet academic standards. Thus, the purpose of this study is to identify ADHD traits and implement effective teaching strategies for ADHD children which can develop their multiple intelligences. Knowing and applying effective methods and strategies for teaching ADHD children are very essential for them to achieve academic success. Therefore, through this research hopefully, teachers can identify ADHD children and implement effective teaching strategies that can develop multiple intelligences for ADHD children optimally. This research is qualitative research with a literature study approach. The results of this research are characteristics of ADHD and effective teaching strategies including assessment and tools that can be used in a classroom that can help to develop 9 multiple intelligences.